Segmental nitrogen doping and carboxyl functionalization of multi‐walled carbon nanotubes. Issue 11 (20th July 2015) - Szekeres, Gergo Peter; Nemeth, Krisztian; Kinka, Aniko; Magyar, Melinda; Reti, Balazs; Varga, Erika; Szegletes, Zsolt; Erdohelyi, Andras; Nagy, Laszlo; Hernadi, Klara
Abstract : Partial nitrogen doping was performed during the catalytic chemical vapor deposition (CCVD) synthesis of multi‐walled carbon nanotubes. A special reactor was created to facilitate the execution of syntheses with different reaction conditions. The synthesized samples were analyzed by transmission electron microscopy (TEM) in order to provide information about the tubular and nontubular morphology of particles and their deformation gained after the reaction conditions were changed. The incorporation of nitrogen into the carbon structure was studied by X‐ray photoelectron spectroscopy (XPS), whereas X‐ray diffraction (XRD) and Raman spectroscopy evaluations showed the degree of graphitization. The samples then were carboxyl functionalized in varied concentrations of nitric acid solutions and photosynthetic reaction center protein (RC‐26) purified from purple bacteria was linked to the carboxyl groups in order to make the degree of functionalization visible. The protein‐linked samples were characterized by atomic force microscopy (AFM). Our experiments indicated that the syntheses carried out in the new reactor were successful and resulted in carbon nanotubes partially doped with nitrogen. TEM studies revealed that the expected deformations are localized only in a defined segment of carbon nanotubes therefore nitrogen doping is most possibly presented there. The nitrogen content in the samples represented in atomic ratios was between 0.9% and 2.9%. The deformations facilitate the functionalization at that certain area, thus the location of carboxyl groups can be determined.